TRANSREGIONAL PARTNERSHIP OF BRICS IN RUSSIAN STUDIES - A. A. Konkin (MGIMO University Press, 2016)
This article reviews the literature dealings with the problems of the BRICS, summarized the issues raised by various authors on the main trends in the development of the community and this organization in generally in light of the global economic and political processes. Issues theoretical aspects of further development of the organization as one of the vectors of the global redistribution of the globally weight. This research consistently served all major aspects, related to the functioning of the features of the BRICS as an innovative format of the informal inter-regional cooperation between the countries. So far as the BRIXis a relatively "young"association, its institutionalization is a currently ongoing. This is the primarily due to the economic aspect: the creation of the New Development Bank completes the first stage of the creation BRICS how the formalized association. In contrast to the economic component, around which, most likely, will build further cooperation, political institutionalization seems a distant prospect. At least, included in the Community countries are very different politically and are in completely different conditions in the international political arena. Perhaps in the future the BRICS will move purely in the economic vector. The paradox of this situation lies in the fact that the country's economic data are also very different. Their "weight" in the world economy has a rather significant that carries a precondition for the emergence of some of the dominant structure in the BRICS format. In this aspect, it all depends on future market component of the external and internal environment of each country. Under their influence will be shaped and altered their economies and unexpected moments can occur in a turbulent global economic space. Russian authors studied in detail the characteristics of each of the member countries of BRICS, which allows to mark a significant interest in the national science to the study of inter-regional cooperation in the global political and economic space. At the same time, the study of bibliography dedicated to the problems of the BRICS, cannot be accommodated of the entire volume of literature because there are large numbers of their, so the focus is on the main issues raised by various researchers. Disclosed issues of mutually beneficial cooperation of the participating countries in the format of this organization.